Is There a Minimum Effective Dose for Vascular Occlusion During Blood Flow Restriction Training? - Das, Arpan; Paton, Bruce (Frontiers in Physiology, 2022)
Background: Blood flow restriction (BFR) training at lower exercise intensities has a range of applications, allowing subjects to achieve strength and hypertrophy gains matching those training at high intensity. However, there is no clear consensus on the percentage of limb occlusion pressure (%LOP) and percentage of one repetition max weight (%1RM) required to achieve these results. This review aims to explore what the optimal and minimal combination of LOP and 1RM is for significant results using BFR. Method: A literature search using PubMed, Scopus, Wiley Online, Springer Link, and relevant citations from review papers was performed, and articles assessed for suitability. Original studies using BFR with a resistance training exercise intervention, who chose a set %LOP and %1RM and compared to a non-BFR control were included in this review. Result: 21 studies met the inclusion criteria. %LOP ranged from 40% to 150%. %1RM used ranged from 15% to 80%. Training at 1RM ≤20%, or ≥80% did not produce significant strength results compared to controls. Applying %LOP of ≤50% and ≥80% did not produce significant strength improvement compared to controls. This may be due to a mechanism mediated by lactate accumulation, which is facilitated by increased training volume and a moderate exercise intensity. Conclusion: Training at a minimum of 30%1RM with BFR is required for strength gains matching non-BFR high intensity training. Moderate intensity training (40-60% 1RM) with BFR may produce results exceeding non-BFR high intensity however the literature is sparse. A %LOP of 50-80% is optimal for BFR training.